Pentingnya Peran Orang Tua Dan Guru Terhadap Pencegahan Cyber Bullying Pada Ypi. Hj. Animah Ar-Raihan Martubung Medan - Ilvira, Muhsin Lambok; Damayanti, Erni; Amaniarsih, Dwi Suci; Sari, Revita (LPPM Universitas Potensi Utama, 2022)
The entry of Era Society 5.0, as a form of resolution from resolution 4.0, where community social relations are not only limited to direct meetings (face to face), but can also be done through interaction through social media, where in this era digitalization in every activity can be used/ used to support human needs with the aim that humans can live more comfortably and more effectively, not reducing the number of bullying cases that occur in the community, especially in the school social environment. Bullying cases in this digitalization era are known as Cyber ??Bullying. The KPAI Data Bank stated that there were 361 cases of child victims of cyber bullying during 2016-2020, and it is possible that there were cases of cyber bullying that were not reported. With this number, it can be said that bullying behavior in the era of society can occur, this is possible because many children are already able to use gadgets. The implementation of this Community Service is carried out in the form of legal counseling by providing legal knowledge related to Cyber ??Bullying and the importance of the role of parents and teachers in preventing cuber bullying. The results of the Service stated that parents and teachers have a very very important role in preventing cyber bullying behavior, because from home children will see examples which then in interacting with their friends will be used, because children are easier to imitate what they see, while at school too. Apart from that, good control over the use of gadgets and their positive use is also a good education for children.